2021
DOI: 10.1186/s13098-021-00733-5
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The best drug supplement for obesity treatment: a systematic review and network meta-analysis

Abstract: Background Obesity is a complex disease with an increasing prevalence worldwide. There are different weight-management options for obesity treatment, including dietary control, exercise, surgery, and medication. Medications are always associated with different responses from different people. More safety and efficacy of drugs with fewer side effects are valuable for any clinical condition. In this systematic review and network meta-analysis, different anti-obesity drugs are compared to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Topiramate, a gamma-aminobutyric acid (GABA) receptor agonist, decreases appetite and increases satiety. It is often used for the treatment of epilepsy and migraine headaches [20,21]. The combination of phentermine with topiramate has been approved by FDA for the management of obesity.…”
Section: Phentermine-topiramatementioning
confidence: 99%
See 1 more Smart Citation
“…Topiramate, a gamma-aminobutyric acid (GABA) receptor agonist, decreases appetite and increases satiety. It is often used for the treatment of epilepsy and migraine headaches [20,21]. The combination of phentermine with topiramate has been approved by FDA for the management of obesity.…”
Section: Phentermine-topiramatementioning
confidence: 99%
“…Liraglutide is a subcutaneous GLP-1 agonist, which is used daily for the management of diabetes mellitus type 2 and obesity/weight management [20]. A systematic review and meta-analysis by Khera et al found that 23% of participants taking placebo had a weight loss of 5% compared to 63% of those taking liraglutide (OR 5.54, 95% CrI 4.16-7.78, SUCRA 0.83).…”
Section: Liraglutidementioning
confidence: 99%
“…Other studies suggest that this drug combination modulates dopaminergic expression [ 73 ]. Based on the safety and clinical efficacy analysis of drugs for treating obesity, bupropion is on the list of drugs that can effectively reduce body weight [ 74 ].…”
Section: Novel Drugs In Obesity Treatmentmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the Table 2 reports incorrect data for some of the studies included in the analysis: In the study by Davies et al (row 3), the dose of liraglutide should read 3.0 mg instead of 0.3 mg. In the study by Greenway et al (row 6), it should read Naltrexone 16.0 mg + bupropion instead of Naltrexone + bupropion 16.0 mg, and Naltrexone 32.0 mg + bupropion instead of Naltrexone + bupropion 32.0 mg. In the study by O’Neil et al (row 9) it should read Lorcaserin 10 mg BID instead of Orlistat 120.mg BID, and Lorcaserin 10 mg QD instead of Orlistat 120.mg QD. …”
Section: Correction To: Diabetol Metab Syndr (2021) 13:110 101186/s13...mentioning
confidence: 99%